Optimal HIIT Workout Dosage for Weight Loss in Sedentary Adults - Grayson Kayla Rakkan (Universitas Pejuang Republik Indonesia, 2026)
Backgroud: High-Intensity Interval Training (HIIT) has emerged as a time-efficient alternative exercise modality to moderate-intensity continuous training (MICT) in an effort to lose weight and body fat in sedentary populations. Methods: This article systematically reviews the current literature on the most optimal doses of HIIT training (frequency, session duration, intensity, and work-rest ratio) for weight loss in adults who were previously physically inactive. Searches were conducted on PubMed, ScienceDirect, and Google Scholar databases for relevant randomized clinical trials (RCTs), meta-analyses, and systematic reviews. Results: The results of the synthesis showed that HIIT programs run for more than 8 weeks, a minimum of 3 sessions per week, with work intervals of less than 60 seconds separated by active recovery ≤90 seconds were shown to be more effective in producing beneficial changes in body composition. In addition, HIIT with a volume of ≥75 minutes per week showed advantages over the control group in indicators of body fat percentage, waist-to-hip circumference, and VO₂max, so it could be considered for short-term fat loss. The effects of HIIT on fat loss and cardiorespiratory fitness in young and middle-aged adults are equal to or better than MICT, which is influenced by age, obesity complications, duration of intervention (>6 weeks), frequency, and length of HIIT intervals. Conclusions: that the optimal HIIT dosage for the sedentary population ranges from a frequency of 3 times/week, the duration of the program is more than 8 weeks, with a weekly volume of at least 75 minutes, although it is necessary to make gradual adjustments given the characteristics of a population that has not been adapted to high-intensity exercise.